Additive manufacturing of novel ferritic stainless steel by selective laser melting: Role of laser scanning speed on the formability, microstructure and properties. (August 2021) - Jiang, P.F.; Zhang, C.H.; Zhang, S.; Zhang, J.B.; Chen, J.; Chen, H.T.
Highlights: Selective laser melted novel stainless steel was prepared by various laser scanning speed. Appropriate choice of laser scanning speed would help improve the formability of novel stainless steel. Microstructure features, corrosion behavior and wear property were correlated with laser scanning speed. The corrosion morphplogy analysis confirmed the key parameters affecting to corrosion performance. Abstract: Novel ferritic stainless steel was successfully fabricated by selective laser melting (SLM) technology. This study was dedicated to the effect of laser scanning speed on the formability, microstructural evolution, wear and corrosion performance of SLM novel stainless steel. The results showed that the densification level of the SLM specimens was significantly improved with the increase of laser energy density due to the reduction in pore defects. The microstructure of the SLM specimens was mainly composed of α-Fe, with a small amount of Cr23 C6 . The EBSD pattern of the SLM specimens showed anisotropy due to complex thermal convection in the SLM process. The proportion of the LAGBs and α-Fe increased with the increase of laser scanning speed while the average grain size decreased from 0.481 to 0.467 μm. The SLM specimens possessed excellent properties, with the corrosion resistance significantly higher than that of some common engineering alloys. The best SLM specimen possessed a corrosion potential of −148 mV SCE, a corrosion current density of 1.38 × 10 −7 A cm −2, microhardness of 812 HV, and a specific wear rate of 1.99 × 10 −6 mm 3 /Nm.